Pengukuran Kinerja Program Studi Teknik Industri Universitas Trunojoyo - Retno Indriartiningtias; Titim Ainul Mufid (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
Trunojoyo University, as the only higher education institutions in the Madura District continues determined to always improve performance. The existence of a higher education never ceases to be searched by the public making increasingly tight competition between the University to the Faculty and Department level. Based on the department's performance measurement model there are 40 KPIs are used as an indicator that includes, 5 lectures and lab facilities the KPI, KPI 14 for faculty characteristics, student characteristics KPI 15, KPI and 6 for program majors. The method used in the study is interviews and questionnaires. Respondents in this study are determined by the method of stratified random sampling. Based on the results of performance studies courses in Industrial Engineering Department of Trunojoyo University for 1186 with less category